Surveillance of molecular markers of Plasmodium falciparum artemisinin resistance (kelch13 mutations) in Papua New Guinea between 2016 and 2018. (August 2021) - Lautu-Gumal, Dulcie; Razook, Zahra; Koleala, Tamarah; Nate, Elma; McEwen, Samuel; Timbi, Diana; Hetzel, Manuel W.; Lavu, Evelyn; Tefuarani, Nakapi; Makita, Leo; Kazura, James; Mueller, Ivo; et al.
Abstract: Plasmodium falciparum resistance to artemisinin-based combination therapy (ACT) is a global threat to malaria control and elimination efforts. Mutations in the P. falciparum kelch13 gene ( Pfk13 ) that are associated with delayed parasite clearance have emerged on the Thai-Cambodian border since 2008. There is growing evidence of widespread Pfk13 mutations throughout South-East Asia and they have independently emerged in other endemic regions. In Papua New Guinea (PNG), Pfk13 "C580Y" mutant parasites with reduced in vitro sensitivity to artemisinin have been isolated in Wewak, a port town in East Sepik Province. However, the extent of any local spread of these mutant parasites in other parts of PNG is unknown. We investigated the prevalence of Pfk13 mutations in multiple malaria-endemic regions of PNG. P. falciparum isolates (n = 1152) collected between 2016 and 2018 and assessed for Pfk13 variation by sequencing. Of 663 high quality Pfk13 sequences a total of five variants were identified. They included C580Y, a mutation at a previously documented polymorphic locus: N499K, and three previously undescribed mutations: R471C, K586E and Y635C. All variants were found in single isolates, indicating that these Pfk13 mutations were rare in the areas surveyed. Notably, C580Y was absent from Maprik district, which neighbours Wewak where C580Y mutant parasites were previously identified. The single C580Y isolate was found in the port town of Lae, Morobe Province, a potential entry site for the importation of drug resistant parasites into PNG. Although sample size in this location was small (n = 5), our identification of a C580Y mutant in this second location is concerning, highlighting the urgent need for further surveillance in Lae. Other Pfk13 mutants were rare in PNG between 2016 and 2018. Continued surveillance for molecular markers of drug resistance is critically important to inform malaria control in PNG.